Nrf2 and its dependent autophagy activation cooperatively counteract ferroptosis to alleviate acute liver injury. (January 2023) - Liu, Jiawei; Huang, Chao; Liu, Jianming; Meng, Chao; Gu, Qi; Du, Xinyue; Yan, Minyu; Yu, Yingjie; Liu, Fanglan; Xia, Chunhua
Abstract: Ferroptosis has been implicated in the pathophysiological progression of a variety of diseases. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key regulator of cellular antioxidant response and can counteract ferroptosis by inducing autophagy and targeting genes involved in iron metabolism and glutathione (GSH) synthesis/metabolism. This study investigated how Nrf2 and autophagy interact to prevent ferroptosis in acute liver injury under sulforaphane (SFN) intervention. The results showed that SFN could activate Nrf2 signaling pathway and its downstream target genes, promote cell autophagy, and then combat ferroptosis to alleviate liver injury. After inhibiting Nrf2, the autophagy activated by SFN almost disappeared, and the anti-ferroptosis effect was greatly weakened. After inhibiting autophagy, SFN can still activate Nrf2 and its downstream target gene, but solute carrier family 7 member 11 (SLC7A11) membrane transfer and its cystine transport ability are significantly weakened, thus ultimately attenuating the anti-ferroptosis effect of SFN. Further studies showed that Nrf2-dependent autophagy activation disrupted SLC7A11 binding to S93-phosphorylated coiled-coil myosin-like BCL2-interacting protein (BECN1) and increased SLC7A11 membrane transfer to combat ferroptosis. In conclusion, Nrf2-dependent autophagy activation is essential for promoting SLC7A11 membrane localization to inhibit ferroptosis. Activation of Nrf2 not only upregulates the expression of SLC7A11, glutathione peroxidase 4 (GPX-4) and autophagy-related proteins, but also destroys the binding of SLC7A11 and BECN1 by inducing autophagy, thereby promoting SLC7A11 membrane transfer and GSH synthesis, and finally suppressing ferroptosis. However, inhibition of autophagy had no significant effect on the expression of Nrf2 and downstream genes during SFN anti-liver injury intervention. Graphical Abstract: ga1 Highlights: Nrf2 activation induces the expression of SLC7A11, GPX-4 and autophagy-related proteins. Nrf2-dependent autophagy is essential for promoting SLC7A11 membrane localization to inhibit ferroptosis. Sulforaphane (SFN) can counteract ferroptosis and alleviate acute liver injury through the co-regulation of Nrf2 and autophagy. Autophagy inhibition had no significant effect on the expression of Nrf2 and its downstream genes in SFN anti-liver injury.